Sistem Informasi Approval Magang dengan Metode Workflow Management pada PT. Telkom Akses - Bilbi Huzaimi Mahmuda; Samsudin Samsudin; Laila Nurzanah (Jurnal Publikasi Manajemen Informatika, 2025)
The internship application process at PT Telkom Akses is still done conventionally, where the applicant must apply directly by bringing the application letter to the relevant department. This process involves several stages, including approval from superiors and time-consuming disposition, which can cause inconvenience and uncertainty for the applicant. The Internship Approval Information System is designed to improve efficiency and transparency in the internship application and approval process. The purpose of this information system is to improve the conventional system so that applicants can easily submit applications, receive information about the status of applications, and facilitate managers in monitoring and reporting internship application activities. In designing this system, the Workflow Management method is used to organize a clear and structured workflow, so that each step in the approval process can be carried out systematically and efficiently. The results of this system design are expected to be used as a prototype in developing internship approval information system software that is better, more efficient, and responsive to user needs at PT Telkom Akses.